PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP PRICE EARNING RATIO DAN ROA DENGAN KEPEMILIKAN SAHAM ASING SEBAGAI VARIABEL MODERASI PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Kartawinata ' (JURNAL KOMPETITIF, 2013)
ABSTRACT The purpose of this research is to understand the effect of corporate social responsibility on price earning ratio and ROA of company which is registered in Indonesia Stock Exchange and authorized sustainability report in 2009 and 2010 with foreign ownership as a moderating variable.The sample uses here is the secondary data with purposive sampling method. Corporate social responsibility disclosure data are from sustainability report which are gotten from each official company website. Foreign ownership, price earning ratio and ROA can be gotten from company annual report and can be downloaded at www.idx.co.id. Statistical method uses linear regression and multiplied linear regression. With 5% standard error , can be concluded that corporate social responsibility disclosure doesn’t influence toward price earning ratio and ROA. Foreign ownership doesn’t influence toward the relation between coporate social responsibility disclosure with price earning ratio and doesn’t influence toward the relation between corporate social responsibility disclosure with ROA. Key Words : corporate social responsibility disclosure, price earning ratio, CSRI, ROA, foreign ownership.